Lettres sans réponse : entre le regret, la nostalgie et l’intérêt - Rosalina Estrada Urroz (Les Cahiers ALHIM)
The correspondence that we analyze constitute a way to understand the happy moments, distresses and sadness that invade those that migrate and their families who have the eyes set  on  the ports of departure and of arrival. These feelings cross time and change according to the successes or failures of migration. Alone or deceived women, parents who have lost their economic support; mothers, concubines and wives who remain in France send letters of inquire by their own means or by a third person that have a major authority. To the emotion and sadness of the voyage together with the repeated distress, those that remain in land accompany the trip; the missives are witness of the moment, and  guide, ask and complain because of the absence. The expression of feelings have different meanings, from those one that cry for the absence of their husbands, to the suffering of the grandparents for the well-being of the grandsons that remain alone in Mexican lands.